Incorporating thyroid markers in Down syndrome screening protocols - Dhaifalah, Ishraq; Salek, Tomas; Langova, Dagmar; Cuckle, Howard (Prenatal diagnosis, 2017)
OBJECTIVE: The article aimed to assess the benefit of incorporating maternal serum thyroid disease marker levels (thyroid-stimulating hormone and free thyroxine) into first trimester Down syndrome screening protocols. METHODS: Statistical modelling was used to predict performance with and without the thyroid markers. Two protocols were considered: the combined test and the contingent cell-free DNA (cfDNA) test, where 15-40% women are selected for cfDNA because of increased risk based on combined test results. Published parameters were used for the combined test, cfDNA and the Down syndrome means for thyroid-stimulating hormone and free thyroxine; other parameters were derived from a series of 5230 women screened for both thyroid disease and Down syndrome. RESULTS: Combined test: For a fixed 85% detection rate, the predicted false positive rate was reduced from 5.3% to 3.6% with the addition of the thyroid markers. Contingent cfDNA test: For a fixed 95% detection rate, the proportion of women selected for cfDNA was reduced from 25.6% to 20.2%. CONCLUSIONS: When screening simultaneously for maternal thyroid disease and Down syndrome, thyroid marker levels should be used in the calculation of Down syndrome risk. The benefit is modest but can be achieved with no additional cost. © 2017 John Wiley & Sons, Ltd.
Keywords: Thyroid Diseases; první trimestr těhotenství; Downův syndrom; Sensitivity and Specificity; senzitivita a specificita; Pregnancy; Humans; Thyrotropin; Down Syndrome; Predictive Value of Tests; Prenatal Diagnosis; nemoci štítné žlázy; Female; Thyroid Gland; dospělí; testy funkce štítné žlázy; Thyroxine; lidé; Biomarkers; štítná žláza; Pregnancy Trimester, First; Adult; biologické markery; ženské pohlaví; prediktivní hodnota testů; Cell-Free Nucleic Acids; Thyroid Function Tests; volné cirkulující nukleové kyseliny; prenatální diagnóza; těhotenství; Mass Screening; thyroxin; plošný screening; thyreotropin